The methyl-CpG-binding domain (MBD) is crucial for MeCP2’s dysfunction-induced defects in adult newborn neurons - Zhao, Na; Ma, Dongliang; Leong, Wan Ying; Han, Ju; VanDongen, Antonius; Chen, Teng; Goh, Eyleen L. K. (Frontiers in Cellular Neuroscience, 2015)
Mutations in the human X-linked gene MECP2 are responsible for most Rett syndrome (RTT) cases, predominantly within its methyl-CpG-binding domain (MBD). To examine the role of MBD in the pathogenesis of RTT, we generated two MeCP2 mutant constructs, one with a deletion of MBD (MeCP2-ΔMBD), another mimicking a mutation of threonine 158 within the MBD (MeCP2-T158M) found in RTT patients. MeCP2 knockdown resulted in a decrease in total dendrite length, branching, synapse number, as well as altered spontaneous Ca2+ oscillations in vitro, which could be reversed by expression of full length human MeCP2 (hMeCP2-FL). However, the expression of hMeCP2-ΔMBD in MeCP2-silenced neurons did not rescue the changes in neuronal morphology and spontaneous Ca2+ oscillations, while expression of hMeCP2-T158M in these neurons could only rescue the decrease in dendrite length and branch number. In vivo over expression of hMeCP2-FL but not hMeCP2-ΔMBD in adult newborn neurons of the dentate gyrus also rescued the cell autonomous effect caused by MeCP2 deficiency in dendrites length and branching. Our results demonstrate that an intact and functional MBD is crucial for MeCP2 functions in cultured hippocampal neurons and adult newborn neurons.